3D Parametric Finite Element Model for the Mechanical Simulation of Vertebrae with Metastatic Lesions - Muñoz Allué, Jaime; García Aznar, José Manuel; Pérez Ansón, Mª Ángeles (Jornada de Jóvenes Investigadores del I3A, 2024)
Bone metastases in the spine are very common in cancer patients. A 3D parametric model based on the finite element (FE) method has been developed to study various types of metastatic lesions. Several ex vivo experimental cases were reproduced, and the impact of the bone-tumour interface was investigated.